(untitled) (Research, Society and Development, 2023)
The objective of this study is to report the experience lived by extensionists of the Immunology project in Professional Schools of Fortaleza in an internal training on Vaccines and Covid-19. This is an exploratory and descriptive study, of a qualitative and quantitative nature, carried out through the Google Meet videoconferencing application and the Google Forms survey management application. Students from undergraduate courses in health sciences and biological sciences linked to the extension project participated in the activity, as well as students and professors from postgraduate programs at the Federal University of Ceará (UFC). Among the results, distance communication technologies through the dissemination of didactic content make the teaching and learning process possible, effectively and playfully enabling the transfer of knowledge and interaction between people without the need for direct contact in the same physical environment. Through globalized communication tools, it is possible to ensure effectiveness in learning and disseminating content related to a particular theme. In conclusion, the teaching and learning activity carried out by virtual means was successful. The project public was able to expand knowledge about immunology, focusing on the constituent inputs of the vaccine against Covid-19, promoting the dissemination of knowledge during the online meeting.